2015
DOI: 10.1371/journal.pone.0137091
|View full text |Cite
|
Sign up to set email alerts
|

Visible Persistence of Single-Transient Random Dot Patterns: Spatial Parameters Affect the Duration of Fading Percepts

Abstract: Visible persistence refers to the continuation of visual perception after the physical termination of a stimulus. We studied an extreme case of visible persistence by presenting two matrices of randomly distributed black and white pixels in succession. On the transition from one matrix to the second, the luminance polarity of all pixels within a disk- or annulus-shaped area reversed, physically creating a single second-order transient signal. This transient signal produces the percept of a disk or an annulus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(76 reference statements)
1
3
0
Order By: Relevance
“…if the stimuli include no attribute, integration is altered because the pathway of plasticity is disturbed. A target display to eyes, leaves a trace in the neuronal structures involved in memory [1,2]. In line with previous research, our findings confirm implication of orientation in the discharge of cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…if the stimuli include no attribute, integration is altered because the pathway of plasticity is disturbed. A target display to eyes, leaves a trace in the neuronal structures involved in memory [1,2]. In line with previous research, our findings confirm implication of orientation in the discharge of cells.…”
Section: Discussionsupporting
confidence: 92%
“…The recent evidence demonstrated that the visual system drives original information of an image, and the persistence of this trace on the neuronal memory is ensured by V1 [1]. The continuous effects of the stimuli are correlated with memorization, while trace remains in the cortical circuitry for few seconds [2]. The truth is, visual stimuli composed of many parameters, can affect the behaviour of cortical neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of this type of contour persistence is typically 1–3 s, and contour visibility ends instantaneously when contour elements are physically removed (Ferber, Humphrey, & Vilis, 2003 , 2005 ; Large, Aldcroft, & Vilis, 2005 ; Strother et al, 2011 ; Strother, Lavell, & Vilis, 2012 ), consistent with offset-initiated reset and the prevention of contour “hallucination” in the absence of supporting visual input (Li, 1998 ). The duration of contour persistence is considerably longer than the neural persistence reported by O'Herron and von der Heydt ( 2009 , 2011 ) for figure–ground border-ownership signals in visual cortex (0–1.3 s), and it is also longer than any other type of shape-related visual persistence we are aware of (e.g., Bruchmann, Thaler, & Vorberg, 2015 ; Landman, Spekreijse, & Lamme, 2003 ; O'Herron & von der Heydt, 2011 ; Shioiri & Cavanagh, 1992 ; Supèr, Spekreijse, & Lamme, 2001 ; Wallis, Williams, & Arnold, 2009 ; Wutz, Weisz, Braun, & Melcher, 2014 ). The relatively long duration of contour persistence is remarkable in its own right, and may reflect the size of the underlying neural network (Compte, Brunel, Goldman-Rakic, & Wang, 2000 ; Toyoizumi, 2012 ).…”
Section: Introductionmentioning
confidence: 52%
“…In fact, it was believed that “a retinal afterimage effect” or the controversial theory of the “persistence of vision,” erroneously also called “retinal persistence,” contributed to the concept of that visible persistence. Conversely, visible persistence is now considered a more complex cortical process underlying the continuation of visual perception after the physical termination of a stimulus (Bruchmann and others 2015).…”
Section: Movement and Light Studiesmentioning
confidence: 99%